2022
DOI: 10.1103/physrevb.105.104207
|View full text |Cite
|
Sign up to set email alerts
|

X-ray induced dynamics in borate glasses with different network connectivity

Abstract: Hard x rays induce atomic dynamics in oxide glasses at doses low enough that the average structure is unchanged. X-ray photon correlation spectroscopy is used here to study this effect in a series of alkali borate glasses characterized by different network connectivity. The product of the x-ray dose rate per atom and the decay time of the density correlation function is a sample-dependent parameter with the dimensions of an energy: It varies between a fraction of eV and few tens of eV and is sensitive to the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…Such flux dependent dynamics have been observed before in XPCS experiments on oxide and network glasses 26 29 , albeit with orders of magnitude higher dose rates, and also recently in dense protein glasses 30 . In our case the dynamics of the protein gels are governed by stress relaxations in which the correlation functions can be modeled as a series of consecutive relaxation events in the stressed material 68 , 74 .…”
Section: Resultssupporting
confidence: 74%
“…Such flux dependent dynamics have been observed before in XPCS experiments on oxide and network glasses 26 29 , albeit with orders of magnitude higher dose rates, and also recently in dense protein glasses 30 . In our case the dynamics of the protein gels are governed by stress relaxations in which the correlation functions can be modeled as a series of consecutive relaxation events in the stressed material 68 , 74 .…”
Section: Resultssupporting
confidence: 74%
“…One key point, however, is that the data discussed here show a complex dose and dose rate dependence that has to be disentangled. The dose rate dependence has been discussed in previous studies, where it was shown that the decay time of the intensity correlation functions scales with the inverse of the dose rate ( 1 5 ). For what concerns the dose dependence, in the Inset of Fig.…”
mentioning
confidence: 96%
“…The claim of local fluidization comes from the observation that the density correlation function at the interatomic length scale decays to zero under X-ray irradiation: This is a sign of a complete renewal of the atomic configuration typical of a liquid but not of a glass. The characteristic timescale, τ ( q ), of such configuration renewal turns out to be inversely proportional to the X-ray dose rate ( 1 5 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations